Controversies of Treatment Modalities for Cerebral Venous Thrombosis - Maria Khan; Ayeesha Kamran Kamal; Mohammad Wasay (Stroke Research and Treatment)
Cerebral vein thrombosis has been well recognized for nearly two centuries. However, therapeutic options for the condition are limited due to lack of large randomized trials. The various modalities reportedly used include antiplatelets, anticoagulation, fibrinolysis, and mechanical thrombectomy. Of these, antiplatelets are the least studied, and there are only anecdotal reports of aspirin use. Anticoagulation is the most widely used and accepted modality with favorable outcomes documented in two randomized controlled trials. Various fibrinolytic agents have also been tried. Local infusions have shown more promise compared to systemic agents. Similarly, mechanical thrombectomy has been used to augment the effects of chemical thrombolysis. However, in the absence of randomized controlled trials; there is no concrete evidence of the safety and efficacy of either of these modalities. Limited study series disclosed that decompression surgery in malignant CVT can be life saving and provides good neurological outcome in some cases. Conclusion. Overall therapeutics for CVT need larger randomized controlled trials. Anticoagulaion with heparin is the only modality with a reasonable evidence to support its use in CVT. Endovascular thrombolysis and mechanical thrombectomy are reserved for selected cases who fail anticoagulation and decompression surgery for malignant CVT with impending herniation.